2017
DOI: 10.1177/2309499017718901
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of pedicle screw placement based on preoperative computed tomography versus intraoperative data set acquisition for spinal navigation system

Abstract: Aim: To investigate the accuracy of pedicle screw placement based on preoperative computed tomography in comparison with intraoperative data set acquisition for spinal navigation system. Methods: The PubMed (MEDLINE), EMBASE, and Web of Science were systematically searched for the literature published up to September 2015. This review followed the Preferred Reporting Items for Systematic Reviews and Meta-analysis guidelines. Statistical analysis was performed using the Review Manager 5.3. The dichotomous data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 30 publications
0
16
0
Order By: Relevance
“…However, in this study, the AR and FH techniques showed no significant difference in terms of primary or secondary screw perforation, average MAPW, average doMLCA, or cranio-caudal inclination angle in the hands of the expert surgeons. Several studies demonstrated significantly higher accuracy of pedicle screw placement using other navigation systems providing three-dimensional information to the surgeon compared to the free-hand technique [20,23,24]. Three-dimensional navigation proved to be of use not only in patients with but particularly when treating spinal deformity [25,26].…”
Section: Discussionmentioning
confidence: 99%
“…However, in this study, the AR and FH techniques showed no significant difference in terms of primary or secondary screw perforation, average MAPW, average doMLCA, or cranio-caudal inclination angle in the hands of the expert surgeons. Several studies demonstrated significantly higher accuracy of pedicle screw placement using other navigation systems providing three-dimensional information to the surgeon compared to the free-hand technique [20,23,24]. Three-dimensional navigation proved to be of use not only in patients with but particularly when treating spinal deformity [25,26].…”
Section: Discussionmentioning
confidence: 99%
“…This is in line with recent meta-analyses comparing other types of navigation systems to conventional surgical methods, showing increased accuracy when using navigation 1,5 . Navigation has been demonstrated to have the largest impact on accuracy in complex deformity surgeries, especially in the neuromuscular type of scoliosis 14 , and in the thoracic spine where the pedicles can be very small 15 . Narrow thoracic pedicles, altered by scoliosis, can provide a formidable challenge in spinal instrumentation 8,9,16 .…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, the retrospectively collected data of the control group only included the total procedure time and the fluoroscopy time could not be calculated for comparison. Studies on procedural time using navigation have shown conflicting results, demonstrating both longer 14,15,28 and shorter times 6,29 .…”
Section: Figurementioning
confidence: 99%
“…Implants of the wrong size can ultimately lead to unstable fixation 10 or may lead to pedicle fracture or damage to the nerves and vessels. 7,11,15 For osteoporotic fractures, which are commonly stabilized using cement augmentation, pedicle fractures may lead to cement leaks into the spinal canal. Furthermore, the surgeon should be aware preoperatively of whether sufficient implant material of the correct length and diameter for a stable osteosynthesis is in stock.…”
Section: Discussionmentioning
confidence: 99%
“…Posterior spinal fusion is an important tool in the treatment of patients with spinal trauma or with degenerative disorders like spinal stenosis or spondylolisthesis. [1][2][3][4][5][6][7][8][9] Numerous studies have been aimed at quantifying the ideal biomechanical properties of the implants required to maximize pullout resistance, [10][11][12][13][14] but the optimal trajectory angle for placing pedicle screws remains unclear. While some authors aim for a trajectory that results in the longest possible screw, others favor a position parallel position to the pedicle wall, accepting a decreased insertion depth.…”
Section: Introductionmentioning
confidence: 99%